Performance analysis of a quasi-two stage compression air source heat pump in severe cold region with a new control strategy. (25th June 2020) - Wei, Wenzhe; Ni, Long; Zhou, Chaohui; Yao, Yang; Xu, Laifu; Yang, Yahua
Highlights: A segmented control strategy for ultra-low temperature running was proposed. Heating performance at ultra-low outdoor temperature was investigated. Change trends of injection pressure varied a lot with supply water temperature. 17.33% higher energy efficiency than central heating is obtained. Better economic and environmental benefits in Harbin are predicted. Abstract: The quasi-two stage compression air source heat pump (QTASHP) has been widely used in cold regions, such as North China, but not in severe cold regions due to the excessive discharge temperature at lower ambient temperature. To expand the application of QTASHP in severe cold regions, a novel control strategy was proposed to decrease discharge temperature, and used in a test rig in Harbin. The experimental QTASHP adopted R410A as refrigerant, and was used to supply heat for a lab through heating circulation water. Its heating performance was researched experimentally when outdoor temperature was −27.5 to −10 °C, and supply water temperature was 35–50 °C. Experimental results showed QTASHP could run smoothly under all conditions with the proposed control strategy, and its discharge temperature under the most unfavorable condition was 112.0 °C. Based on experimental results, a numerical research on its heating performance was conducted using the software of DeST, and its economic and environmental benefits were analyzed. Simulation results showed its seasonal coefficient of performance and primary energy efficiency in Harbin were 2.35 and 0.88. Compared with central heating, its pollutants/CO2 emissions decreased by 14.76% and the dynamic payback period was 9.86 years for energy-saving buildings.